Moving beyond the Islamophobic Discourse to Mutual Collaboration: The Case Study of Humanists and Muslims in the United Kingdom, 2012-2019 - Benamer , Hamza; Sahli , Fatiha (Journal of Human Sciences, 2024)
This study reconsiders the controversial relationship between the so-called ‘Humanists’ and ‘Muslims’ in the UK, by suggesting that it is characterized by a mutual collaboration rather than hostility. The terms ’Humanist’ and ‘Secularist’ are used interchangeably to refer to the same school of thought, that of atheism. While it is true that some contemporary scholars have attempted to associate the rising Islamophobic discourse with the secularists, this article, however, offers two hypotheses to prove the opposite. The Humanist movement UK is like a melting pot that encompasses individuals from a variety of denominational and ethnic backgrounds, including Muslims. The other argument is the openness of Humanists and Muslims to foster dialogue and exchange of views on inclusive education and interfaith dialogue. The analysis showed that the religion of Islam represented an important current in humanist culture. Additionally, Humanists and Muslims fully committed themselves to fighting both Islamic and secular extremism by promoting a moderate perspective, through which they created a more inclusive, tolerant, and cohesive social fabric.